Thyroid function in protein-energy malnutrition - Hatemi, Nadir; Haktan, Makbule; Genca, Ertuğrul; Cuma, Tahsin (The Turkish Journal of Pediatrics, 1982)
Thyroid function is investigated in 20 malnourished and 10 normal infants.Our findings indicate that there is a significant decrease in serum thyroid hormone levels in protein-energy malnutrition. After two months of treatment, serum T_4 and FT_4 levels were still significantly lower in the patients than in normal controls. T_3 levels were also significantly low in untreated malnourished infants. After treatment the mean T_3 value of malnourished babies was still lower than in normal controls, but the difference was not statistically significant.It is concluded that decrease in thyroid gland activity in protein-energy malnutrition should be considered as an adaptation to low calorie intake.
Keywords: malnutrition; nutritional disorder; protein energy malnutrition; thyroid function